Xiphinema index and its Relationship to Grapevines: A review - van Zyl, S.; Vivier, M.A.; Walker, M.A. (South African Journal of Enology and Viticulture, 2016)
The dagger nematode, Xiphinema index, is considered a major pest in grape growing countries. Xiphinema index is especially important because of its ability to transmit Grapevine fanleaf virus when feeding on grapevine roots. This paper provides a comprehensive and updated review of the classification, genetics and biology of Xiphinema index, and its relationship with grapevine fanleaf virus. Current control measures, as well as past and present efforts to breed resistant grapevine rootstocks, are presented.